Three essays on heterogeneity in macroeconomics - Diaby, Mohamed (2019)
This doctoral thesis emphasizes the role of Heterogeneity in modern Macroeconomics. First, it provides a new determinant to heterogeneity in firms' price-setting, namely the degree of returns to scale. It provides theoretical and empirical evidence that price rigidity and returns to scale are positively associated. Heterogeneity in price rigidity and returns to scale are then linked. Further, this thesis introduces both dimensions of heterogeneity into an otherwise standard Keynesian model and simulate the real effects of monetary policy shock on output. This thesis also provides evidence that the amplification initially implied by heterogeneity in price rigidity is mitigated when heterogeneity in returns to scale is added. Finally, this thesis explores the heterogeneous effects of macroprudential policy on bank profitability across different income levels. There is evidence that a tightening of macroprudential policy tends to decrease bank profitability in countries where the financial sector is less developed, which is the case for emerging countries.